The potential roles of carotenoids in enhancing phytoremediation of bisphenol A contaminated soil by promoting plant physiology and modulating rhizobacterial community of tobacco. (March 2023) - Fu, Wenting; Zheng, Xiaoyan; Chen, Xiancao; Wang, Wenjing; Liu, Anran; Ji, Jing; Wang, Gang; Guan, Chunfeng
Abstract: The widespread occurrence of bisphenol A (BPA), a typical endocrine-disrupting compound, poses potential threat to ecosystem and public health. Carotenoids are essential natural pigments, playing important roles in photosynthesis and antioxidant defense of plants. This study aimed to verify the value of carotenoids in enhancing plant tolerance to BPA stress and improving phytoremediation efficiency of tobacco ( Nicotiana tabacum L.), through exogenous application of β-carotene (a typical carotenoid) and endogenous upregulation of carotenoids by overexpression of β-carotene hydroxylase ( chyb ) gene in tobacco. The results demonstrated that exogenous applied β-carotene alleviated the toxic effects of BPA exposure (100 mg kg −1 ) on wild-type (WT) tobacco plants after being cultivated for 40 d, reflecting by the increase of biomass (201.2%), chlorophyll content (27.5%) and the decrease of malondialdehyde (MDA) content (70.7%). Similar with the results of exogenous application of β-carotene, chyb gene overexpressing tobacco showed less phytotoxicity exposed to BPA, through enhancing photosynthetic efficiency (42.1%) and reducing reactive oxygen species (ROS) production (18%). Notably, about 94.8% BPA in contaminated soil was removed under the cultivation of transgenic tobacco for 40 d, however, only 82.7% was removed in that of WT tobacco. Moreover, transgenic tobacco is beneficial for the growth of plant roots, thus upregulating the abundance of bacteria contributing to BPA degradation or soil nutrient cycling (e.g., Proteobacteria, Acidobacteria, Actinobacteria, Sphingomonas and MND1 ), which might further help to enhance plant growth and improve BPA removal efficiency in soil. This study extended our understanding of the possible mechanisms of carotenoids-involved alleviation of BPA stress in tobacco, providing a novel strategy to improve phytoremediation efficiency of plants in BPA contaminated soil. Graphical abstract: Image 1 Highlights: The upregulation of carotenoids alleviated toxic effects of BPA on tobacco. Overexpression of chyb gene could increase the content of carotenoids in tobacco. Transgenic tobacco promoted plant tolerance to BPA stress and BPA removal efficiency. Transgenic tobacco reduced damage of BPA to photosynthetic/antioxidant system. BPA-degradable bacteria were enriched in rhizosphere soil of transgenic tobacco.